ARISING OF DIGITAL DIVIDE - DOBIAS, Vaclav (Trends in education, 2015)
The article presents analysis of the international survey ICILS 2013. The main aim of this article is to reveal reasons of rise second level digital divide in the Czech Republic. Results of the questionnaire part of survey ICILS 2013 are presented in the form of contingency tables. The main findings is: Students learn themselves leisure computer activities. At activities leading to work with computers, parents with higher educational attainment more teach their children these activities, so better socioeconomically situated students have higher chance to know the basics working computer activities before starting the learning ICT at school.
Keywords: digital divide; parental educational level; digital literacy; ICILS 2013.